work-life balance, job satisfaction and burnout among university lecturers - Siddiqi, Soha (2021)
To meet the increasing demands of professional as well as private life, maintaining an optimum work life balance has become a necessity. It has been observed that an imbalance between the two has lead to disruption of work and personal life. Juggling between work and life effectively is an overwhelming, yet essential task, especially for those in the teaching field. A good work life balance is reflected by increased levels of job satisfaction, decreased level of burnout and contentment in personal life.